Optimising verapamil hydrochloride floating tablets formula - Vu Van Tuan; Trinh Nam Trung; Nguyen Van Bach (Vietnam Journal of Science, Technology and Engineering, 2025)
This study aimed to optimise the formulation of verapamil hydrochloride (VH) floating tablets to improve bioavailability and sustain drug release. The tablets were prepared using the wet granulation method, and VH quantification was conducted via high-performance liquid chromatography (HPLC). A categorical and continuous factors (CCF) experimental design was employed using Modde Pro 13.1 software, while formulation optimisation was conducted with INForm 3.1 software. The key formulation factors, including the concentrations of hydroxypropyl methylcellulose (HPMC) K4M, HPMC E6, and sodium bicarbonate, were systematically varied to assess their influence on drug release and floating properties. The optimised formulation consisted of 120 mg VH, 59 mg HPMC K4M, 35 mg HPMC E6, 29.3 mg sodium bicarbonate, 50 mg Avicel, 98.7 mg lactose, 8 mg magnesium stearate, and sufficient 10% PVP K30 in 96% ethanol. The in vitro dissolution study demonstrated that the optimised formulation met the United State Pharmacopeia (USP) 47 requirements for extended-release VH tablets, with a similarity factor (f₂) of 92.13 when compared to the predicted release profile. The floating lag time (Tlag) was minimised while ensuring sustained drug release over eight hours. The release kinetics followed the Korsmeyer-Peppas model with a high correlation coefficient (R²=0.997). In conclusion, the optimised VH floating tablet formulation successfully enhances gastric retention and controlled drug release, offering a promising approach for improving the therapeutic efficacy of VH.